2023
DOI: 10.3390/pharmaceutics15061660
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Thermogelling System for Nose-to-Brain Donepezil Delivery: Optimising Formulation Properties and Nasal Deposition Profile

Abstract: Donepezil nasal delivery strategies are being continuously investigated for advancing therapy in Alzheimer’s disease. The aim of this study was to develop a chitosan-based, donepezil-loaded thermogelling formulation tailored to meet all the requirements for efficient nose-to-brain delivery. A statistical design of the experiments was implemented for the optimisation of the formulation and/or administration parameters, with regard to formulation viscosity, gelling and spray properties, as well as its targeted n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Animal implants using Schwann cell-seeded scaffolds showed significantly improved innervation compared with NSC scaffolds. 92 …”
Section: How Do Recently Developed Methods Target Brain Disorders?mentioning
confidence: 99%
See 1 more Smart Citation
“…Animal implants using Schwann cell-seeded scaffolds showed significantly improved innervation compared with NSC scaffolds. 92 …”
Section: How Do Recently Developed Methods Target Brain Disorders?mentioning
confidence: 99%
“…The applications and effects of AM are being studied. 92 4D printing can be performed in two ways. One possibility is to include the transformation of information into the structural design.…”
Section: How Do Recently Developed Methods Target Brain Disorders?mentioning
confidence: 99%
“…Conversely, Perkušić et al reported that drug deposition within the olfactory region was significantly influenced by administration parameters, rather than formulation parameters. 115 Enhanced drug deposition in the olfactory region was achieved with a higher administration angle, ranging from 45° to 75°, when intranasally delivering a chitosan-based temperature-sensitive ISG containing donepezil using the VP7 spray pump in an in-vitro 3D nasal model coated with Sar-Gel ® paste. In addition, olfactory deposition was diminished by an increase in inspiratory flow rate, as breathing and airflow directed the formulation towards the turbinate region.…”
Section: Strategies To Improve Drug Delivery Via the Intranasal Routementioning
confidence: 99%
“…111,112 To address these limitations, researchers have studied how to predict drug deposition in the nasal cavity using in-vitro 3D models that mimic human nasal conditions or in-vivo models. 101,[113][114][115] This section discusses drug deposition in the nasal cavity after intranasal administration of ISGs using a nasal device.…”
Section: Drug Deposition Of In-situ Gel Formulations In the Nasal Cavitymentioning
confidence: 99%
“…Thereby, they ensure drug immobilization into a highly viscous layer, adherence to the target region, and a sustainable effect. The usage of in situ gelling vehicles is highly appropriate in the development of nasal dosage forms for local, systemic, or nose-to-brain drug delivery [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%